(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In the conditions of modern economic instability and global crisis phenomena, enterprises are forced to look for new approaches to preserving and strengthening their positions in the market. One of the most effective directions for forming an anti-crisis strategy is the introduction of modern information technologies into marketing activities. The purpose of the article is research into the role of modern information technologies in the formation and implementation of an enterprise’s anti-crisis marketing strategy. Methods. The use of methods of analysis and synthesis, comparison and theoretical generalization allowed us to investigate the features of the application of modern information technologies in the marketing activities of enterprises in times of crisis, as well as to substantiate their role as an effective tool of anti-crisis strategy. Results. The article defines the essence of anti-crisis management in the context of managing the strategic capabilities of an enterprise, describes the classification of modern information technologies in marketing, and characterizes the features, advantages, and disadvantages of Internet marketing as an element of an enterprise’s anti-crisis marketing strategy. Conclusions. Modern information technologies as a tool of the enterprise’s anti-crisis strategy provide flexibility, efficiency and accuracy of marketing decisions in conditions of instability. The implementation of digital tools allows you to effectively adapt to market changes, optimize costs and increase competitiveness.